Development of A Learning Management System (Lms) as A Learning Media For High School And Equivalent - septia, fandy (Jurnal Tata Rias, 2019)
This research uses the Research and Development method, also defined as research that is deliberately, systematically aimed/directed to find, formulate, improve, develop, produce, test the effectiveness of products, models, methods/strategies/ways, services, and certain procedures that are superior, new, effective, efficient, productive, and meaningful. The development model used is the 4D development model. This 4D model consists of 4 main stages, namely, define, design, development, and disseminate. The Learning Management System (LMS) was developed as a learning medium using open-source software. It is expected to attract students' attention, provide motivation to students, and be tailored to students' interests, so that it is hoped that the information conveyed through the media can be captured by students and tested in the teaching and learning process to see the practicality of using the Learning Management System (LMS). LMS encompasses administration, material delivery, assessment, monitoring, and communication. Materials in pedagogical and professional competencies, created using multimedia packaging (text, animation, video, sound) in the LMS, will accelerate the mastery of science and technology, thereby optimally improving the quality of learning.